Dampak Campuran Bahan Bakar Oktan 92, 95 dan Eco Racing terhadap Kinerja Mesin dan Emisi Gas Buang - Nur, Mulyadi; Erna Wahyu P., Agnes (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2020)
Makassar aviation polytechnic is a high school under the Indonesian Ministry of Transportation, with the main task of carrying out a professional Diploma program in aviation engineering and safety. One of the study programs in the aviation engineering department is Aircraft Maintenance Technology Study Program, which studies all parts of the aircraft as well as maintaining and repairing the aircraft so that it can fly safely to its destination. One obstacle that occurred in the Aircraft Maintenance Technology study program at POLTEKBANG is unavailability of fuel, the Avgas used on the Piston Enggine aircraft so the learning or peractic processes can’t realize were carried out due to the absence of fuel sold in the area. South Sulawesi therefore has to order in the East Java Province of Surabaya resulting in higher costs. The need of gasoline fuel as fossil energy is increasing and essential for daily life, occurs because of scarcity, can not be renewed and pollute to damage the ozone layer so it is important to do research to get optimal engine performance and low emissions. The reseach conducted for learning process or Peractum can accordance with the existing curriculum in the Makassar TPT POLTEKBANG with a pure fuel measurement test on the engine with a compression ratio of 11.3: 1 and varying the mixture of RON 92, RON 95 and Eco Recing, at 4,000 to 10,000 Rpm rotation. The result of the emission test according to the standard, can be explained that the best result is the use of fuel octane 92 with CO: 0.52% and HC: 125 ppm, capable of producing optimal power and torque compared to octane 95. The best mix variation is a ratio of 90: 10 producing maximum power up to 14.5 Hp and torque of 12.97 Nm